Hepatitis B assays in serum, plasma and whole blood on filter paper - Mayer, Theodor K (BioMed Central, 2012)
BACKGROUND: Screening and determining the immune status of individuals for hepatitis B is usually done by detecting hepatitis B surface antigen (HBsAg) and hepatitis B surface antigen-specific antibodies (HBsAb). In some countries with the highest viral burden, performing these assays is currently impractical. This paper explores the use of filter paper as a blood specimen transport medium. METHODS: Samples, chosen from routine clinical laboratory pool, were applied and dried onto filter paper. Eluates, from the paper samples, were analyzed as routine clinical specimens on ADVIA Centaur 5634® immunoassay analyzers using the standard HBsAg and HBsAb kits. Dried blood samples were subjected to a range of environmental conditions in order to assess stability. RESULTS: After drying and elution the assays showed linearity and precision comparable to clinical assays performed on fresh serum. Elutions at various times during a 149 day incubation period showed very little variability in the Index numbers. All analytes were temperature stable except for a decrease in the HBsAg signal at 42°C. CONCLUSIONS: Filter paper is an acceptable storage and transport medium for serum to be used in the detection of hepatitis B markers if atmospheric variability can be controlled. HBsAg, HBsAb and HBcAb are all stable for at least five months under storage conditions below room temperature. Drying specimens, particularly serum, on filter paper at remote locations, offers a reasonable solution to the problem of hepatitis surveillance in underdeveloped regions, although some attempt at temperature control might be desirable.